Improving ferroelectricity and ferromagnetism of PVDF‐CoFe2O4 thick films: Effect of Ethyl acetate and Temperature. Issue 6 (5th August 2019) - Wang, Libo; Su, Yuchang; Zhang, Jing; Zhang, Hongzhi; Dong, Qiaoqiao
ABSTRACT: PVDF‐CoFe2 O4 (CFO) thick membranes were synthesized by solvent casting method. The mixed organic solvents consist of N‐methyl‐2‐pyrrolidone (NMP) and Ethyl acetate (EA), in which the mass ratios of NMP and EA (NMP:EA = 1:0, 1:1, and 1:2) and the temperature of solvent evaporation (range from 50 to 80 °C) has been considered. The phase structure, β‐PVDF phase content, and electrical and magnetic properties of these membranes were investigated to reveal the effect of EA addition and temperature on these properties. Results manifest that all samples showed coexistence of ferroelectric and ferromagnetic properties at room temperature. EA addition makes film more compact, which may be responsible for the differences in ferromagnetic properties. Adding EA and enhancing temperature resulted in phase transition of PVDF from α and γ to β, which contributed to membranes' ferroelectric performances. In all samples, NMP:EA = 1:2 treated at 80 °C exhibits the maximum β‐phase fraction and polarization (Pmax) of 87.2% and 2.398 μC cm −2, respectively. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48345. Abstract :